DSC of human hair: a tool for claim support or incorrect data analysis?. (15th February 2016) - Popescu, C.; Gummer, C.
Abstract: Differential scanning calorimetry (DSC) data are increasingly used to substantiate product claims of hair repair. Decreasing peak temperatures may indicate structural changes and chemical damage. Increasing the DSC, wet peak temperature is, therefore, often considered as proof of hair repair. A detailed understanding of the technique and hair structure indicates that this may not be a sound approach. Surveying the rich literature on the use of dynamic thermal analysis (DTA) and differential scanning calorimetry (DSC) for the analyses of human hair and the effect of cosmetic treatments, we underline some of the problems of hair structure and data interpretation. To overcome some of the difficulties of data interpretation, we advise that DSC acquired data should be supported by other techniques when used for claim substantiation. In this way, one can provide meaningful interpretation of the hair science and robust data for product claims support. Abstract : Thermal analysis of the hair provides unique hints about its structure and effect of treatments. No matter what type of thermal analysis experiment is used, data cannot be evaluated per se and supportive experimental techniques are required for any claim support.